2020
DOI: 10.3390/ijerph17176128
|View full text |Cite
|
Sign up to set email alerts
|

Combating Fear of Missing Out (FoMO) on Social Media: The FoMO-R Method

Abstract: Background: The fear of missing out (FoMO) on social media refers to the apprehension that online content and interactions from others are unseen and reacted to in a timely fashion. FoMO can become problematic, leading to anxiety, interrupted sleep, lack of concentration and dependence on social media to generate gratification. The literature has mainly focused on understanding the FoMO experience, factors contributing to it and its consequences. Method: In this paper, we build on previous research and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 66 publications
3
77
1
15
Order By: Relevance
“…Given that we showed that the latter may have a detrimental effect on young adults' mental health because of its positive correlation with both FOMO and loneliness, a possible intervention is to encourage the use of messaging and VoIP apps, while discouraging passive social network usage, during periods of physical isolation. Previous research has shown that mental well-being can be enhanced with socio-technical approaches aimed at reappraisal of FOMO (e.g., self-talk, checklists; Alutaybi et al, 2020 ), as well as cognitive reappraisal of time spent alone (e.g., reappraise their time alone as solitude rather than loneliness; Rodriguez et al, 2020 ). Thus, public policy interventions encouraging young adults to adopt approaches that help them manage negative experiences such as FOMO or perceived isolation could greatly help reduce their negative consequences on mental health, especially in highly stressful situations that trigger a compulsive use of technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that we showed that the latter may have a detrimental effect on young adults' mental health because of its positive correlation with both FOMO and loneliness, a possible intervention is to encourage the use of messaging and VoIP apps, while discouraging passive social network usage, during periods of physical isolation. Previous research has shown that mental well-being can be enhanced with socio-technical approaches aimed at reappraisal of FOMO (e.g., self-talk, checklists; Alutaybi et al, 2020 ), as well as cognitive reappraisal of time spent alone (e.g., reappraise their time alone as solitude rather than loneliness; Rodriguez et al, 2020 ). Thus, public policy interventions encouraging young adults to adopt approaches that help them manage negative experiences such as FOMO or perceived isolation could greatly help reduce their negative consequences on mental health, especially in highly stressful situations that trigger a compulsive use of technology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that these presumed effects of social network usage primarily apply to passive usage (e.g., scrolling), as opposed to active usage (e.g., uploading content). Although not all use of social networking apps is passive, researchers have argued that most of the features that make up their design, such as content personalization, notifications and alerts, as well as content that expires after a set amount of time (e.g., Instagram stories displayed only for 24 h), do encourage compulsive checking that triggers and sustains feelings of FOMO (Alutaybi et al, 2018 , 2020 ). One explanation for these relations is that social network use exacerbates FOMO because social media users can modify the way other people see their profiles, and social media users strive to present a perfect image of who they are for self-presentation and impression management (Crabtree and Pillow, 2018 ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Although there are still no empirical results to confirm this theory, Alutaybi et al ( 2020 ) point out that certain FOMO motivations (e.g. wanting popularity or possessing information) can lead to unhealthy behaviors, such as cyberstalking.…”
Section: Fear Of Missing Out and Cyberstalkingmentioning
confidence: 99%
“…For example, if an individual feels that they are using social media excessively on their smartphone, then the smartphone itself can be used to monitor that behaviour and to deliver appropriate interventions, or alternative forms of support. In our previous research, we have demonstrated that people both desire and accept such systems for digital addiction and related phenomena such as fear of missing out and social media facilitated procrastination [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%